THE CONCEPT TRAINING OF FUTURE MASTERS OF TOURISM IN HIGHER EDUCATION INSTITUTIONS - Bezkorovaina, Larysa V. (Educological discourse, 2017)
The article substantiates that the methodological basis of professional training of future masters of tourism have an approaches: systemic, structural, acmeology, the activity, the operational, praxeology, competence, cultural, information, innovation, value, creative personality; and also, principles of general didactics (humanization, democratization, activity, scientific, systematic, knowledge of the sequence of skills, awareness, communication theory and practice, independence, clarity, thoroughness, availability of training, taking into account individual characteristics of students, emotional learning, a combination of collective and individual, spirituality) and special (citizenship, communication, interdisciplinary, multilevel, continuity, bustling, multicultural, social relevance, feasibility and socio morphic) principles teaching. Also, the study found that the training of future masters of tourism is so important: social; personal; culturological; humanitarian; political. Substantiating the concept of training of future masters of tourism, we made sure that this training is holistic educational system that is based on an integrated approach to designing the content, harmonious combination of traditional and modern computer-oriented methods and teaching aids, and conventional forms of distance educational process; and personal approach that provides not only a comprehensive development of future masters of tourism, but the gradual formation of readiness for professional tourism activity according to individual capabilities, abilities, personal qualities and academic achievements.